Terrorism and U.S. foreign policy - Pillar, Paul R., 1947- (Brookings Institution Press, 2001)
In this critical study, a career CIA officer provides a guide to constructing and executing counterterrorist policy, urging that it be formulated as an integral part of broader U.S. foreign policy.